Effect of pH on effluent organic matter removal in hybrid process of magnetic ion-exchange resin adsorption and ozonation. (February 2020) - Chen, Zhiqiang; Tang, Yingcai; Wen, Qinxue; Yang, Boxuan; Pan, Yang
Abstract: It is essential to mitigate the risk of exposure to effluent organic matter (EfOM) in aquatic environments to ensure safe wastewater recycling. Magnetic ion-exchange (MIEX) resin adsorption combined with ozonation could provide EfOM removal. However, the poor understanding of the influences of the parameters and mechanisms in the hybrid process has restricted the applications. In this study, the response surface methodology was used to reveal the interactions of the major operation parameters. The degradation behaviour of the EfOM was investigated by using spectroscopy combined with mathematical methods. The effect of the pH on the EfOM removal was also analysed. The maximum efficiency of the removal of dissolved organic carbon (DOC) was 59.77% at the optimal MIEX resin dosage of 7.97 mL/L, ozone concentration of 8 mg/L, agitation speed of 199.84 r/min, and pH of 9.98. The ozonation was superior to resin adsorption in the removal of 1054-Da compounds, while the resin adsorption was advantageous in the removal of 4168-Da compounds. Three fluorescent components (C1, C2, and C3) were more easily subjected to external perturbation than the DOC and ultraviolet absorbance at 254 nm in the oxidation processes. The MIEX resin exhibited low efficiencies of removal of the fluorescent substances. A synchronous fluorescence analysis coupled with a two-dimensional correlation analysis revealed that the variation in EfOM followed the order of fulvic-to humic-like substances in the hybrid process of MIEX and the following ozonation. The pH was the most significant influencing factor in the hybrid process. Graphical abstract: Image 1 Highlights: A comprehensive research of MIEX and ozonation removing EfOM in SE was carried out. MIEX-ozonation process was recommended for EfOM removal. pH is the major influencing factor for EfOM removal in the hybrid process. 2D-COS and EEM-PARAFAC were integrated to characterise EfOM evolution. Possible mechanism of pH affecting EfOM removal was proposed.